The Urgency of Privacy Protection in the Era of Digitalization: Challenges and Solutions to Cyber Crime Comparative Legal Studies - CHRISTY, GRACESY PRISELA; Maiercherinra Daud; Ni Putu Noni Suharyanti; Christine Attang; Ade Batti’ (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The Industrial Era 4.0 in Indonesia is characterized by automation and easy connections. Technological advances have had a major impact on changes in people's habits. According to Article 28G paragraph (1) of the 1945 Constitution of the Republic of Indonesia, every person has the right to protection of himself, his family, his honour, honor and dignity, as well as the property he controls. The ease of transactions using online payment media has triggered cyber crimes such as data theft, hacking and system break-ins which are increasing along with the increasing use of digital technology. Cybercrime, such as personal data leakage, identity theft, and financial loss, can have a major impact on society and organizations. The research method used is normative juridical. The conclusion of this research is the effectiveness of implementing laws to protect personal data in Indonesia, how these regulations can ward off cyber crimes which are increasingly widespread in Indonesia based on applicable laws and regulations from the threat of fear of doing or not doing something that is a human right.”  This can be corrected by adopting several personal data regulations from several developed countries which have proven effective in preventing public data leaks which pose a very high risk to banking and company accounts. The formulation of Effective Regulations on the protection of personal data from Cyber Crime must consider the Essence and Scope of Personal Data, the principles of data protection, the obligations of the managing organization, the rights of Individuals, Supervision and law enforcement and the Harmonization of integration with applicable witnesses such as: administrative fines, Restrictions or Prohibitions on Operations, criminal liability, civil damages, and publication of violations